Olive Leaves and Hibiscus Flowers Extracts-Based Preparation Protect Brain from Oxidative Stress-Induced Injury - Elda Chiaino; Matteo Micucci; Sandro Cosconati; Ettore Novellino; Roberta Budriesi; Alberto Chiarini; Maria Frosini (MDPI AG, 2020)
Oxidative stress (OS) arising from tissue redox imbalance, critically contributes to the development of neurodegenerative disorders. Thus, natural compounds, owing to their antioxidant properties, have promising therapeutic potential. Pres phytum (PRES) is a nutraceutical product composed of leaves- and flowers-extracts of Olea europaea L. and Hibiscus sabdariffa L., respectively, the composition of which has been characterized by HPLC coupled to a UV-Vis and QqQ-Ms detector. As PRES possess antioxidant, antiapoptotic and anti-inflammatory properties, the aim of this study was to assess its neuroprotective effects in human neuroblastoma SH-SY5Y cells and in rat brain slices subjected to OS. PRES (1-50 µg/mL) reverted the decrease in viability as well as the increase in sub-diploid-, DAPI-and annexin V-positive-cells, reduced ROS formation, recovered the mitochondrial potential and caspase-3 and 9 activity changes caused by OS. PRES (50-100 µg/mL) neuroprotective effects occurred also in rat brain slices subjected to H2O2 challenge. Finally, as the neuroprotective potential of PRES is strictly related to its penetration into the brain and a relatively good pharmacokinetic profile, an in-silico prediction of its components drug-like properties was carried out. The present results suggest the possibility of PRES as a nutraceutical, which could help in preventing neurodegenerative diseases.